All-Fiber Wideband Supercontinuum Generation in Short Hybrid Highly Nonlinear Fibers With a Femtosecond Erbium-Doped Fiber Laser - Zhang, Shuang; Qiao, Hao; Zhang, Tao; Zhou, Min; Xu, Xinye (Frontiers in Physics, 2022)
Wideband supercontinuum (SC) generation has attracted considerable attention due to its various practical applications in many fields. We report on all-fiber SC generation in hybrid highly nonlinear fibers (HNLFs) pumped with a femtosecond erbium-doped fiber laser (EDFL). Based on the nonlinear polarization rotation (NPR) technique, the EDFL is compactly constructed with a hybrid device integrating a wavelength-division multiplexing (WDM) coupler, a tap coupler, and a polarization-sensitive isolator. The SC emission in HNLFs with different dispersions is characterized and the optimum length of HNLF is found. The SC in the hybrid HNLF, constructed by two sections of HNLFs with positive and zero dispersions, could approximately span an octave spanning in the 20 dB bandwidth. Our system suggests an inexpensive, effective and compact construction for SC generation.